Survival of Staphylococcus epidermidis in Propofol and Intralipid in the Dead Space of Intravenous Injection Ports. (July 2019) - Noble, Ronan M. N.; Salim, Saad Y.; Walker, Bradley; Khadaroo, Rachel G.; Chiarella, Angelo B.; Gragasin, Ferrante S.; Bourque, Stephane L.
Abstract : We tested whether propofol or Intralipid inoculated with Staphylococcus epidermidis would promote bacterial growth within an intravenous (IV) injection hub, a site prone to bacterial contamination. In tubes incubated under optimal conditions, S epidermidis exhibited growth in Intralipid, but not in propofol. In contrast, within the IV hub incubated with either propofol or intralipid at room temperature, S epidermidis bacterial numbers declined with time, and virtually no contamination remained after 12 hours. These data suggest that certain IV lines are inhospitable for S epidermidis .